2023
DOI: 10.1021/jacs.3c03604
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of the Inverse Vulcanization of Elemental Sulfur: Structural Characterization of Poly(sulfur-random-(1,3-diisopropenylbenzene))

Abstract: Organosulfur polymers, such as those derived from elemental sulfur, are an important new class of macromolecules that have recently emerged via the inverse vulcanization process. Since the launching of this new field in 2013, the development of new monomers and organopolysulfide materials based on the inverse vulcanization process is now an active area in polymer chemistry. While numerous advances have been made over the last decade concerning this polymerization process, insights into the mechanism of inverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 71 publications
1
36
0
Order By: Relevance
“…Hence, to interrogate the correct microstructure of deutero poly­(S- r -DIB), structural analysis was conducted after reductive degradation of S–S bonds in the copolymer using LiAlH 4 , followed by in situ acylation of thiols with proteo acetic anhydride, which facilitated recovery of the stable thioester degradation products. This reductive protocol was applied to both proteo and deutero poly­(S- r -DIB) (50 and 70 wt % sulfur), which allowed for isolation of the three primary degradation products and comparisons of their relative ratios between (1) proteo and deutero and (2) weight %S on microstructure composition (our first NMR microstructural characterization of proteo poly­(S- r -DIB) focused only on 50 wt % copolymer composition) . Isolation of the proteo and deutero thioacetate functional degradation products were conducted by silica gel chromatographic isolation of the degraded organosulfur units to enable structural identification of the deutero poly­(S- r - d 14 -DIB) copolymer microstructure using 1 H NMR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, to interrogate the correct microstructure of deutero poly­(S- r -DIB), structural analysis was conducted after reductive degradation of S–S bonds in the copolymer using LiAlH 4 , followed by in situ acylation of thiols with proteo acetic anhydride, which facilitated recovery of the stable thioester degradation products. This reductive protocol was applied to both proteo and deutero poly­(S- r -DIB) (50 and 70 wt % sulfur), which allowed for isolation of the three primary degradation products and comparisons of their relative ratios between (1) proteo and deutero and (2) weight %S on microstructure composition (our first NMR microstructural characterization of proteo poly­(S- r -DIB) focused only on 50 wt % copolymer composition) . Isolation of the proteo and deutero thioacetate functional degradation products were conducted by silica gel chromatographic isolation of the degraded organosulfur units to enable structural identification of the deutero poly­(S- r - d 14 -DIB) copolymer microstructure using 1 H NMR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…These important differences in the microstructures of proteo vs deutero poly­(S- r -DIB) and between 50 and 70 wt % sulfur compositions established from the degradation efforts prompted us to launch detailed computational studies using density functional theory calculations (DFT) as we reported previously for the proteo -DIB inverse vulcanization . These calculations used tetrasulfane (H–S–S–S-S • ) and α-methylstyrene (MeSty) as model compounds for the inverse vulcanization of S 8 and proteo -DIB.…”
Section: Resultsmentioning
confidence: 99%
“…In order to better understand the structure of these polymer, an NMR characterisation using the method developed by Pyun et al was attempted. 20 In short, this method involves breaking down the polymer with LiAlH 4 and analysing the degradation products, which in Pyun et al 's case, were monomeric units of the polymer (see the ESI, section IX† for the full method). Here this analysis method seems not to have worked so effectively.…”
Section: Resultsmentioning
confidence: 99%
“…recently found evidence that polymers of 1,3-diisopropenylbenzene do not react as was initially thought; rather than radical addition across the double bond to create two new C–S bonds, a more complex mechanism dominates, resulting primarily in a linear polymer unit where each double bond produces one new C–S bond. 20 Whether reactions with alkynes could be subject to the same sort of mechanism is unknown, but because Pyun's new findings centre around the formation of thiocumyl moieties and there seems there is no intuitive way such a moiety could form from an inverse vulcanised polymer of an alkyne, it will be initially assumed that radical addition as traditionally expected of inverse vulcanisation occurs here. 20 Furthermore, it cannot be that all co-monomers in inverse vulcanisation are subject to this new mechanism proposed by Pyun, because if that were the case, styrene would not be able to form an inverse vulcanised polymer, but it is documented that it can.…”
Section: Introductionmentioning
confidence: 99%
“…Lai et al have demonstrated the reaction of 1,3,5-triisopropylbenzene with sulfur, noting that this monomer contains no alkenes and sulfur bonds directly to alkyl units . The Pyun group have also built on this work by reassessing their original structure for 1,3-diisopropenylbenzene, demonstrating a different structure formation than was previously suggested . This revisiting of old hypotheses is of great importance for understanding this complex process.…”
mentioning
confidence: 80%